1996
DOI: 10.1210/en.137.2.540
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in resting levels of corticosterone is not mediated by variation in adrenal responsiveness to adrenocorticotropin but involves splanchnic nerve integrity

Abstract: To study possible mechanisms controlling diurnal changes in corticosterone (CORT) levels, we tested the CORT responses to ACTH in the morning (AM) and evening (PM) in male Wistar and Sprague-Dawley rats. Rat ACTH-(1-39) or human ACTH-(1-24) (3.75-15 ng/rat) was given as an iv bolus or an intraarterial infusion to (un)anesthetized rats treated with dexamethasone (0.1-0.5 mg/kg, 2-6 h before ACTH). In all conditions studied, no AM/PM differences in CORT responses were found when ACTH was given in vehicle (pH 4.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The role of VIP in the adrenal glands is not entirely clear; functional studies have demonstrated a response by VIP to ACTH administration and splanchnic nerve stimulation as well as effects of VIP on glucocorticoid secretion by the adrenal glands [28, 34, 35]. Splanchnic denervation in rats has been shown to influence the diurnal rhythm of corticosterone production, either by sympathetic signals to directly induce corticosterone production or in adapting the adrenal responsiveness to ACTH [36]. This suggests that some form of interaction between the HPA axis and the autonomic nervous system controls corticosterone rhythmicity.…”
Section: Discussionmentioning
confidence: 99%
“…The role of VIP in the adrenal glands is not entirely clear; functional studies have demonstrated a response by VIP to ACTH administration and splanchnic nerve stimulation as well as effects of VIP on glucocorticoid secretion by the adrenal glands [28, 34, 35]. Splanchnic denervation in rats has been shown to influence the diurnal rhythm of corticosterone production, either by sympathetic signals to directly induce corticosterone production or in adapting the adrenal responsiveness to ACTH [36]. This suggests that some form of interaction between the HPA axis and the autonomic nervous system controls corticosterone rhythmicity.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting, adaptation to discrete repeated stressors during the light phase was not mediated by ACTH (21). This effect may be mediated via the autonomic nervous system, in particular via the splanchnic nerve that acts during the AM but not the PM to inhibit adrenal responsiveness to ACTH (23–25).…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions the contribution of the sympathetic nervous system on circulating glucocorticoid levels appears to be limited to times when HPA responses are extremely low relative to sympathetic responses. For example, during circadian fluctuations when the diurnal amplitude in plasma ACTH is extremely small, splanchnicectomy reduces peak circulating corticosterone levels (Dijkstra et al, 1996; Ulrich-Lai et al, 2006). Another example is following stressors that do not acutely stimulate HPA responses such as dehydration stress when corticosterone responses can again be blocked by splanchnicectomy (Ulrich-Lai and Engeland, 2002).…”
Section: Introductionmentioning
confidence: 99%